Neutron diffraction studies of a double-crystal (+n, -m) setting containing a fully asymmetric diffraction geometry (FAD) of a bent perfect crystal (BPC). (11th January 2017) - Mikula, P.; Vrána, M.; Šaroun, J.; Em, V.
Abstract : In this paper, some results of neutron diffraction properties of the double-crystal Si(111) + Si(311) setting containing two bent perfect crystals, but with the second one – analyzer in the fully asymmetric diffraction geometry are presented. Both fully asymmetric diffraction geometries, with the output beam compression as well as the output beam expansion, were tested for the sake of possible applications.